Workplace Recreational Strategies and Employee Happiness in Tertiary Institutions in Rivers State, Nigeria (Eurasian Journal of Humanities and Social Sciences, 2022)
Low morale and work related stress have been reported among academic staff of federal government-owned universities in Nigeria. The purpose of this study, therefore, was to examine the correlation between workplace recreational strategies and employees’ happiness in tertiary institutions in Rivers State, drawing our empirical analysis from the academic staff of University of Port Harcourt in South-South Nigeria. The survey research design was considered appropriate to the study. Primary data were collected from academic staff who willingly participated in the through completing a wellstructured questionnaire method. Statistical tools for data analyses included simple percentage, mean scores and standard deviation as well as Pearson Product Moment Correlation method. The study revealed absence of wellness promotion program, inadequate modern recreational facilities for staff leisure and relaxation, absence of sponsored leisure travel for its academic staff which did promote or support academic staff happiness. The study concluded that the current recreational strategies of Uniport as an institution did not promote good leisure culture and relaxation for academic staff’s happiness. In the light of the findings and conclusions of the study, it was recommended that modern recreational facilities and sponsored leisure travel should be provided.